Exercise capacity and its determinants among postcardiac rehabilitation patients with coronary heart disease - Sek Ying Chair; Kai Chi Leung; Sally Wai Sze Lo; Qun Wang; Janet Wing Hung Sit; Sui Yuen Leung; Ho Yu Cheng (Wiley, 2023)
Abstract Aim To investigate the determinants of exercise capacity in postcardiac rehabilitation patients with coronary heart disease (CHD). Design A cross‐sectional design was used. Methods This study analysed the cross‐sectional data from the baseline assessment of 130 CHD patients who participated in a longitudinal randomized controlled trial of music‐paced physical activity intervention for CHD patients (ChiCTR‐IOR‐17011015) (September 2017 to February 2019). Exercise capacity was measured by using the 10‐metre incremental shuttle‐walk test. The amount of physical activity, exercise self‐determination and exercise self‐efficacy were measured by validated instruments. Participants' anthropometric parameters (body mass index, body fat mass percentage and waist circumference) were measured. Hierarchical regression analyses were used to identify the factors influencing exercise capacity. Results The mean incremental shuttle‐walk test distance was 493.00 ± 180.04 m. The factors significantly associated with exercise capacity were age (β = −.42), female (β = −.35), body mass index (β = −.25) and exercise self‐efficacy (β = −.20). These factors accounted for 56.5% of the total variance of exercise capacity.